Strategi Rekruitmen dan Seleksi SDM Pada Perusahaan PT Sumber Bintang Rejeki Semarang - Wau, Windi Dharmayanti; Nugraheni, Krisnawati Setyaningrum (ITB AAS Indonesia Surakarta, 2025)
This research aims to examine the HR recruitment and selection performance strategy at PT Sumber Bintang Rejeki Semarang Company. The study employs a qualitative approach using direct observation and in-depth interviews. This research focuses on understanding how the company implements its recruitment and selection strategies to obtain qualified human resources.The findings reveal that PT Sumber Bintang Rejeki Semarang implements a structured recruitment and selection process through several key strategies. First, the company conducts a comprehensive analysis of organizational needs before initiating recruitment, particularly when addressing employee resignations or planning new branch openings. Second, the company develops detailed candidate profiles based on technical skills, experience, and specific educational requirements. Third, they implement competency-based interviews to evaluate candidates' capabilities and potential based on past behaviors and relevant experiences. Finally, the company employs a thorough onboarding and integration program to ensure new employees can adapt effectively to the company environment.The research concludes that while PT Sumber Bintang Rejeki Semarang has established a systematic approach to recruitment and selection, they still face challenges in attracting candidates with specific expertise and experience. The study recommends enhancing recruitment strategies by focusing on comprehensive candidate assessment, competency-based selection processes, and effective employee integration programs to improve the quality of recruited personnel.